5.25.7 Problems 601 to 700

Table 5.1111: Second order, Linear, Homogeneous and constant coefficients

#

ODE

Mathematica

Maple

15316

\[ {}y^{\prime \prime }+2 y^{\prime }-24 y = 0 \]

15317

\[ {}y^{\prime \prime }-25 y = 0 \]

15318

\[ {}y^{\prime \prime }+3 y^{\prime } = 0 \]

15319

\[ {}4 y^{\prime \prime }-y = 0 \]

15320

\[ {}3 y^{\prime \prime }+7 y^{\prime }-6 y = 0 \]

15321

\[ {}y^{\prime \prime }-8 y^{\prime }+15 y = 0 \]

15322

\[ {}y^{\prime \prime }-8 y^{\prime }+15 y = 0 \]

15323

\[ {}y^{\prime \prime }-8 y^{\prime }+15 y = 0 \]

15324

\[ {}y^{\prime \prime }-9 y = 0 \]

15325

\[ {}y^{\prime \prime }-9 y = 0 \]

15326

\[ {}y^{\prime \prime }-9 y = 0 \]

15327

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = 0 \]

15328

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

15329

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = 0 \]

15330

\[ {}25 y^{\prime \prime }-10 y^{\prime }+y = 0 \]

15331

\[ {}16 y^{\prime \prime }-24 y^{\prime }+9 y = 0 \]

15332

\[ {}9 y^{\prime \prime }+12 y^{\prime }+4 y = 0 \]

15333

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = 0 \]

15334

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = 0 \]

15335

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = 0 \]

15336

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

15337

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

15338

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

15339

\[ {}y^{\prime \prime }+25 y = 0 \]

15340

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 0 \]

15341

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 0 \]

15342

\[ {}y^{\prime \prime }-4 y^{\prime }+29 y = 0 \]

15343

\[ {}9 y^{\prime \prime }+18 y^{\prime }+10 y = 0 \]

15344

\[ {}4 y^{\prime \prime }+y = 0 \]

15345

\[ {}y^{\prime \prime }+16 y = 0 \]

15346

\[ {}y^{\prime \prime }+16 y = 0 \]

15347

\[ {}y^{\prime \prime }+16 y = 0 \]

15348

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

15349

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

15350

\[ {}y^{\prime \prime }-4 y^{\prime }+13 y = 0 \]

15351

\[ {}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0 \]

15352

\[ {}y^{\prime \prime }-y^{\prime }+\left (\frac {1}{4}+4 \pi ^{2}\right ) y = 0 \]

15535

\[ {}y^{\prime \prime }+36 y = 0 \]

15536

\[ {}y^{\prime \prime }-12 y^{\prime }+36 y = 0 \]

15538

\[ {}y^{\prime \prime }-36 y = 0 \]

15539

\[ {}y^{\prime \prime }-9 y^{\prime }+14 y = 0 \]

15543

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

15544

\[ {}y^{\prime \prime }+3 y = 0 \]

15549

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 0 \]

15552

\[ {}y^{\prime \prime }-8 y^{\prime }+25 y = 0 \]

15554

\[ {}y^{\prime \prime }+y^{\prime }-30 y = 0 \]

15555

\[ {}16 y^{\prime \prime }-8 y^{\prime }+y = 0 \]

15562

\[ {}y^{\prime \prime }+20 y^{\prime }+100 y = 0 \]

15564

\[ {}y^{\prime \prime }-5 y^{\prime } = 0 \]

15599

\[ {}y^{\prime \prime }-9 y = 0 \]

15602

\[ {}y^{\prime \prime }-8 y^{\prime }+17 y = 0 \]

15604

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 0 \]

15605

\[ {}y^{\prime \prime }+8 y^{\prime }+17 y = 0 \]

15793

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 0 \]

15794

\[ {}y^{\prime \prime }+9 y^{\prime } = 0 \]

15795

\[ {}x^{\prime \prime }+2 x^{\prime }-10 x = 0 \]

15797

\[ {}y^{\prime \prime }-12 y^{\prime }+40 y = 0 \]

15822

\[ {}y^{\prime \prime }-y^{\prime }-12 y = 0 \]

15823

\[ {}y^{\prime \prime }+9 y^{\prime } = 0 \]

15835

\[ {}16 y^{\prime \prime }+24 y^{\prime }+153 y = 0 \]

15844

\[ {}y^{\prime \prime }+4 y^{\prime }-5 y = 0 \]

15845

\[ {}y^{\prime \prime }-6 y^{\prime }+45 y = 0 \]

16177

\[ {}y^{\prime \prime }-y = 0 \]

16178

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

16180

\[ {}y^{\prime \prime }+9 y = 0 \]

16181

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 0 \]

16182

\[ {}y^{\prime \prime }+9 y = 0 \]

16186

\[ {}y^{\prime \prime }+10 y^{\prime }+24 y = 0 \]

16187

\[ {}y^{\prime \prime }+16 y = 0 \]

16188

\[ {}y^{\prime \prime }+6 y^{\prime }+18 y = 0 \]

16190

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 0 \]

16191

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = 0 \]

16192

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 0 \]

16193

\[ {}y^{\prime \prime }+10 y^{\prime }+25 y = 0 \]

16194

\[ {}y^{\prime \prime }+9 y = 0 \]

16195

\[ {}y^{\prime \prime }+49 y = 0 \]

16200

\[ {}a y^{\prime \prime }+b y^{\prime }+c y = 0 \]

16206

\[ {}y^{\prime \prime } = 0 \]

16207

\[ {}y^{\prime \prime }-4 y^{\prime }-12 y = 0 \]

16208

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]

16209

\[ {}y^{\prime \prime }+3 y^{\prime }-4 y = 0 \]

16210

\[ {}y^{\prime \prime }+8 y^{\prime }+12 y = 0 \]

16211

\[ {}y^{\prime \prime }+5 y^{\prime }+y = 0 \]

16212

\[ {}8 y^{\prime \prime }+6 y^{\prime }+y = 0 \]

16213

\[ {}4 y^{\prime \prime }+9 y = 0 \]

16214

\[ {}y^{\prime \prime }+16 y = 0 \]

16215

\[ {}y^{\prime \prime }+8 y = 0 \]

16216

\[ {}y^{\prime \prime }+7 y = 0 \]

16217

\[ {}4 y^{\prime \prime }+21 y^{\prime }+5 y = 0 \]

16218

\[ {}7 y^{\prime \prime }+4 y^{\prime }-3 y = 0 \]

16219

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = 0 \]

16220

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 0 \]

16221

\[ {}y^{\prime \prime }-y^{\prime } = 0 \]

16222

\[ {}3 y^{\prime \prime }-y^{\prime } = 0 \]

16223

\[ {}y^{\prime \prime }+y^{\prime }-12 y = 0 \]

16224

\[ {}y^{\prime \prime }-7 y^{\prime }+12 y = 0 \]

16225

\[ {}2 y^{\prime \prime }-7 y^{\prime }-4 y = 0 \]

16226

\[ {}y^{\prime \prime }-7 y^{\prime }+10 y = 0 \]

16227

\[ {}y^{\prime \prime }+36 y = 0 \]

16228

\[ {}y^{\prime \prime }+100 y = 0 \]